NATIONAL LIBRARY PLANNING AND UNIVERSAL AVAILABILITY OF PUBLICATIONS - Vickers, Stephen (1977)
Universal Availability of Publications (UAP)means the availability to any individual, wherever he may be, of. any document that he may require, no matter where or when it was published. While such an objective would seem to represent an enormous undertaking, it is merely a statement of one of the basic functions of the service of a library to its clientele. This objective now enjoys the full support·of IFLA and Unesco; but why are such an objective and an associated programme necessary?